Amendment and Soil Type Controls Water-Soluble Phosphorus Recovery from Manure. Issue 20 (12th November 2020) - Ripplinger, Hunter; Sigdel, S.; Chatterjee, A.
ABSTRACT: A laboratory incubation study was conducted for 35 days to determine the water-soluble phosphorus (WSP) recovery from manure treated soils as influenced by four amendments, spent lime, gypsum, leonardite, and alum. For soil with pH 8.1, WSP of control (soil+manure) increased from 40.1 to 61.8 mg kg −1 on 35 d, application of alum, leonardite, spent line, and gypsum reduced the WSP to 0.15 mg kg −1 (99%), 13.3 mg kg −1 (78%), 34.1 mg kg −1 (45%), and 39.8 mg kg −1 (36%), respectively. Soil with pH 6.7, control had initial WSP of 40.9 mg kg −1 and increased to 80.3 mg kg −1 on 35 d, spent lime, alum, gypsum, and leonardite reduced WSP to 23.6 mg kg −1 (71%), 27.4 mg kg −1 (66), 33.5 mg kg −1 (58%), and 61.1 mg kg −1 (24%), respectively. Alum worked for both soils but the performance of other amendments depends on soil pH and concentration of exchangeable calcium and aluminum.